Maternal social representations about communicating the health status of children in the Neonatal Unit (Research, Society and Development, 2022)
Objective: To apprehend maternal representations in the face of knowledge about the severity of children hospitalized in a Neonatal Intensive Care Unit. Method: An exploratory, qualitative study, based on the Theory of Social Representations, through a semi-structured interview, carried out with 10 mothers who accompanied their children in the NICU, carried out in March 2016. The data were analyzed using the Analysis of Contents. Results: After analyzing the speeches of the 10 participants, representations emerged regarding the feeling of fear, anguish and sadness for knowing about the hospitalization in the Neonatal Intensive Care Unit, in addition to the difficulty of information and quality of communication with the health team. Conclusion: Maternal representations were related to: the quality of information on the children's health condition and the difficulty in communication, distancing the maternal figure from co-occupation, protagonism and participation in treatment. Thus, planning family-centered care and improving the information provided, avoiding the use of technical terms, reduce the anguish and stress caused by waiting for prolonged treatment.